2015
DOI: 10.3758/s13414-015-0900-y
|View full text |Cite
|
Sign up to set email alerts
|

Titchener’s ⊥ dissected

Abstract: In three experiments, two independent samples of 12 observers each visually inspected modified versions of Titchener's ⊥ from which the T-junctions had been deleted. For Experiment 1, the ⊥'s two lines had been replaced by dashed lines not meeting in a common point; for Experiment 2, the ⊥ had been reduced to five dots, representing the original lines' end-and midpoints; and for Experiment 3 (in which the second sample of observers served), the ⊥ had been dissected into two separate lines, differently spaced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…This explanation also agrees with the claim that within-object comparisons are easier (faster, more accurate) than between-objects comparisons (Behrmann, Zemel, and Mozer, 1998). Moreover, a recent HVI study used dissected T-shape showed that for upright dissected T-shape, the observed HVI strength was still around 10% (Landwehr 2015(Landwehr , pp. 2150.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…This explanation also agrees with the claim that within-object comparisons are easier (faster, more accurate) than between-objects comparisons (Behrmann, Zemel, and Mozer, 1998). Moreover, a recent HVI study used dissected T-shape showed that for upright dissected T-shape, the observed HVI strength was still around 10% (Landwehr 2015(Landwehr , pp. 2150.…”
supporting
confidence: 86%
“…The most common way of demonstrating the HVI is perhaps to use the length comparison paradigm, with various line configurations, such as L-shape, inverted T-shape, cross, dissected T-shape, etc. (Avery and Day 1969;Cormack and Cormack 1974;Houck et al 1972;Künnapas 1955Künnapas , 1957Landwehr 2015;Prinzmetal and Gettleman 1993). In addition to the length comparison paradigm, the HVI was also demonstrated by length perception per se, i.e.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The predictions were fulfilled: Relative to what had been observed with dissected ⊥s (Landwehr, 2015), the overestimation of the length of the ⊥'s undivided line was enhanced when this line was dotted, and the other line consisted of two dots only (going from 5.13% to 9.23% for the 3 cm gap, and from 2.23% to 3.88% for the 10 cm gap). Conversely, when the divided line was dotted and the undivided line empty, the ⊥-illusion vanished (going from 2.23% to 0.46% for the 3 cm gap), or, for the 10 cm gap, it even reversed (going from 2.23% to −5.99%).…”
Section: Discussionmentioning
confidence: 67%
“…And even so, as noticed by a 5-ms sampling rate on a touch-sensitive computer screen, a somewhat arbitrary decision has to be made on what to use as the subject's response (Landwehr, 2014(Landwehr, , p. 1154. Nevertheless, once a set of criteria is consistently applied, reliable data can be obtained (Landwehr, 2015(Landwehr, , 2016.…”
Section: Introductionmentioning
confidence: 99%